(untitled) (Nigerian Journal of Technology, 2016)
Black cotton soil is highly notorious for its negative effect on engineering construction either as a sub grade material or material under the foundation of buildings. The engineering properties of the soil are adversely affected by the extreme poor nature of the soil. One of such properties is the compressibility of the soil. Regrettably, little emphasis has been placed on this property of the soil. To attempt to proffer solution to this problem, this research investigated the use of sawdust ash and lime on the compressibility characteristics of the black cotton soil. This was achieved by subjecting the soil to one dimensional consolidation. Other tests such as Atterberg’s limits, specific gravity and particle size distribution were also carried out on the soil sample. Sawdust ash was used as additive and it was varied in 0, 4, 8, 12, 16 and 20% by weight of black cotton soil while lime of 4% by weight of the dry soil was also added to all the mixed samples throughout the duration of the consolidation experiment after it proved to be the most effective when added initially to the black cotton soil in various percentages ranging from 0 to 10% by weight of the black cotton soil. Analysis of the results obtained from the laboratory tests conducted on the soil samples and various mix proportions show that there were significant improvements in the compressibility characteristics of the black cotton soil when a combination of 16%SDA and 4%lime of the weight of black cotton soil were added to it. http://dx.doi.org/10.4314/njt.v35i4.5